Risk factors of inguinal hernia: a one-year retrospective study - Aryal, Rishi Kant; Thapa, Nirmal; Shrestha, Prabin; Maharjan, Suresh (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: An inguinal hernia occurs when tissue protrudes from the abdominal cavity through the inguinal canal. While several theories have been proposed regarding their origin, larger datasets on inguinal hernia incidence can help clarify its pathophysiology. This study aimed to identify the various types of inguinal hernias observed at our center and to investigate the associated risk factors.Methods: This retrospective study included 318 cases of inguinal hernia from February 2024 to February 2025. Complaints recorded were groin swelling with or without pain, family history, lifestyle choices, recurring constipation, bladder issues, and cough. Diagnosis relied on visible groin swelling or a palpable abdominal wall defect.Results: Out of 318 adult patients, 294 were male and 24 female, with a significant difference (P < 0.01). The most common age group was 40–49 years (27% males, 45.74% females), followed by 50–59 years (22% males, 20.83% females). Most patients (58.5%) experienced swelling for less than a year; 7.1% for over two years. There was a significant difference (p